Optimal selection of measurement locations for parameter estimation in distributed processes - Uciński, Dariusz (Zielona Góra: Uniwersytet Zielonogórski)
The problem of locating pointwise sensor measurements so as to optimally estimate unknown parameters in a class of distributed systems is studied. Based on a scalar measure of performance defined on the corresponding Fisher information matrix, two approaches are developed for this problem: introduction of continuous designs, which allows for adaptation of well-known sequential algorithms of classical optimum experimental design, and application of standard non-linear programming techniques.
Keywords: sensor location; distributed-parameter systems; parameter estimation; optimum experimental design; spatial statistics